2016
DOI: 10.1016/j.jaci.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Current application of exhaled nitric oxide in clinical practice

Abstract: Disclosure of potential conflict of interest: J. Malka has received payment for lectures and travel support from Aerocrine and Mead Johnson. S. J. Szefler has consultant arrangements with Roche, AstraZeneca, Aerocrine, Daiichi Sankyo, Boehringer Ingelheim, Merck, Genentech, and Novartis and has received grants from GlaxoSmithKline. J. D. Spahn declares that he has no relevant conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 10 publications
1
29
1
1
Order By: Relevance
“…Despite these limitations, results of this study generally support the patterns observed in clinical studies . As noted in the 2011 ATS guidelines and by others assessing the clinical utility of FeNO, no single measure can be used to assess and manage asthma, which is a complex, episodic, and variable disease . When combined with physical examination and other asthma assessment tools, FeNO measurement can provide an additional data point that may be useful for clinicians in asthma management.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Despite these limitations, results of this study generally support the patterns observed in clinical studies . As noted in the 2011 ATS guidelines and by others assessing the clinical utility of FeNO, no single measure can be used to assess and manage asthma, which is a complex, episodic, and variable disease . When combined with physical examination and other asthma assessment tools, FeNO measurement can provide an additional data point that may be useful for clinicians in asthma management.…”
Section: Discussionsupporting
confidence: 80%
“…A primary contribution of this analysis of a nationally representative, population‐based sample of children with asthma is to increase understanding of the variation of FeNO levels in a non‐clinical setting. Because NHANES is a multipurpose health survey, these findings can neither support nor refute observed associations between FeNO and more precisely defined outcomes found in clinical studies (such as risk of frequent medication use or prediction of an asthma exacerbation) . There are also limitations to consider when comparing results to those obtained in clinical studies.…”
Section: Discussionmentioning
confidence: 84%
“…The significant decrease of FeNO under dupilumab may be interpreted as a marker of interleukin (IL)-4/IL-13 blockade as the NO is produced with chronic airways inflammation. 7 Conjunctivitis was reported in up to 28% of patients. [1][2][3]8 IL-4/IL-13 blockade may increase the activity of the OX40 ligand involved in atopic keratoconjunctivitis.…”
mentioning
confidence: 99%
“…As previously indicated, this set of biomarkers has proved useful in selecting initial step therapy in infants and children and, combined with the presence of patient characteristics, such as eczema and race/ethnicity, can help determine next-step therapy if there is an inadequate response to low-dose ICSs. [17][18][19][34][35][36] The challenge will now be to identify new biomarkers that can prove even better than the ones we now have available. Perhaps this will come from a systems biology approach that uses the various ''omics'' techniques combined with careful phenotyping of patients.…”
Section: Identifying Biomarkers and Biologics To Alter The Course Of mentioning
confidence: 99%